Creep behavior of gold thin films investigated by bulge testing at room and elevated temperature. Issue 1 (22nd October 2018) - Merle, Benoit
Abstract: Abstract : The creep behavior of 200-nm thick gold films was investigated by plane-strain bulge testing between 23 and 100 °C. The polycrystalline gold films were produced by thermal evaporation and their columnar microstructure was stabilized by a preliminary heat treatment at 120 °C. The creep tests were performed at constant stress values between 80 and 300 MPa over 12 h, using a custom-built bulge tester. The stress exponent calculated from the creep data decreased from 4.3 to 2.8 between 23 and 100 °C, suggesting a possible transition in deformation mechanisms. The stress exponent and activation energy measured around room temperature point toward the climb of dislocations at grain boundaries being the rate-limiting deformation mechanism. Above 75 °C, scanning electron microscope inspections of tested membranes suggest an increased contribution of diffusion and of grain-boundary mediated deformation, as evidenced by the formation of grooves along grain boundaries. This is presumably the reason for the decrease of the apparent stress exponent and sudden increase of the apparent activation energy.